Power quality based optimal nodal pricing in tradable electricity market - Umale, Virendra; Warkad, Sanjay (International Journal of Engineering and Technology, 2018)
Optimal Power Flow method described the nodal transmission pricing into different related factors, such as congestion,generation, power and electric load limitations. These detailsof each bus transmission prices can be used for to improve the proper usage of transmission congestion and power grid and to get reasonable transmission pricing for power structure. The proposed methodology is demonstrated on IEEE57 bus system and Maharashtra utility electric 400/765kv network.